Two roads for oncolytic immunotherapy development - Howard L. Kaufman; Praveen K. Bommareddy (Journal for ImmunoTherapy of Cancer, 2019)
Abstract Oncolytic viruses are an emerging class of immunotherapy agents for cancer treatment. In this issue of JITC, Machiels et al. reports early phase data from an oncolytic adenovirus given by intravenous (IV) administration. While this may allow easy access to metastatic lesions, there is limited data supporting the therapeutic effectiveness of this approach. Further studies should include assessment of viral replication in tumor tissue and consider comparative trials using IV and intratumoral delivery to fully optimize oncolytic immunotherapy.